V-Lab vs Real Lab in Protein Content Test Experiments - E Ervina; B Supriatno; R Riandi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
This study aims to compared virtual lab with real lab. The experimental research design was used in this study. Compared two different treatments in the experiment testing the protein content in food materials. This study resulted in differences in results between laboratory trials by virtual lab procedures with virtual labs. This research was also conducted on real laboratories that produce differences (1) facts showed in virtual laboratories and real laboratories, (2) the process of changes that occur in experiments. The virtual lab can’t present all objects/event that appears in the real lab. In conclusion the real lab more potential to appeared concrete and relevant facts than virtual lab.